ANALISIS FAKTOR KEMACETAN TERHADAP KINERJA LALU LINTAS DI RUAS JALAN JENDERAL BASUKI RAHMAT (STUDI KASUS: MALL BASSURA) - Hafidzsyah Alfiana; Adhi Purnomo (LOGISTIK, 2020)
Commercial buildings in the Bassura Mall area (Jalan Jenderal Basuki Rahmat) have resulted in congestion in the area. Vehicles use road bodies to park their vehicles, sidewalks that are used as trading places by street vendors, and the position of the entrance / exit of Bassura Mall for four-wheeled vehicles that is not strategic. These things have caused the author to choose a location in the Bassura Mall area (Jalan Jenderal Basuki Rahmat), East Jakarta which is a local route, where East Jakarta as one of the big cities in the Special Capital Region of Jakarta also experiences high vehicle growth, p. This can be seen on roads in East Jakarta which often experience congestion during rush hour. The purpose of this research is to determine the traffic performance in the area. The method used in this research is direct observation method at the research location and field data collection in the form of parking volume data, pedestrian volume, vehicle volume entering / exiting Mall Bassura, traffic volume, and road performance. Observations were made on weekdays and holidays. The results of the analysis of the performance of the road sections show that the traffic volume on the roads around Mall Bassura is 32,433 SMP / hour on weekdays and 22,577 SMP / hour on holidays, with the service level index being in the F category on weekdays and holidays. Thus, the congestion factors mentioned above have resulted in a decrease in road capacity which has an impact on road performance.